Social skills in smokers: a study with brazilian undergraduate students (Brazilian Journal of Behavioral and Cognitive Therapy, 2015)
The objective of this study was to compare characteristics of social skills on college smokers and nonsmokers. We evaluated 1126 students enrolled in a public university in western São Paulo through a questionnaire - the Fagerström test for nicotine dependence - and the Social Skills Inventory (Inventário de Habilidades Sociais) - IHS (Del Pret-te & Del Prette , 2001) . Smokers had, on average, higher scores on the factor score F1 in the IHS when compared to nonsmokers. The data do not confirm the hypothesis of an association between social skills deficits and smoking among participants of this research. College smokers have been described, on average, as more assertive when com-pared to nonsmokers. More studies to confirm this information is still required. Prospective and/or tranversal researches on the possible underlying factors to the association between smoking and assertiveness may also contribute to understanding of the subject.
Keywords: smoking; social skills; assertiveness